Protective effects of myrtenol against paraquat-induced toxicity in rats - Fatemeh Amin; Hosein Basirat; Najmeh Parvaz; Morteza Khademalhosseini; Elham Hakimizadeh; Iman Fatemi (BMC Pulmonary Medicine)
Abstract Background Paraquat (PQ) is a widely used pesticide, can cause severe intoxication and respiratory failure. Myrtenol (Mrl), an essential oil derived in various plants, exhibits several biological properties, including anti-inflammatory and antioxidant activities. This study aims to investigate the protective potential of Mrl against oxidative stress and inflammation caused by PQ exposure. Methods Twenty-five Wistar albino rats were divided into the following groups (n = 5 in each group): a control group (treated by dimethyl sulfoxide (DMSO)), a PQ group (exposed to 54 mg/m³ aerosol PQ), and two treatment groups that were exposed to PQ aerosol and administered oral Mrl at doses of 25 mg/kg/day and 50 mg/kg/day, respectively. The final group was exposed to PQ aerosol and treated with oral dexamethasone at a dose of 0.03 mg/kg/day. Various hematological, oxidative, inflammatory, and pathological indices were measured at the conclusion of the treatment period. Results PQ decreases the levels or activities of superoxide dismutase (SOD), catalase (CAT), and Thiol, while increasing the levels or activities of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and malondialdehyde (MDA). Mrl restored activites of SOD, and CAT, as well as thiol levels to near-control values while reducing TNF-α, IL-6, and MDA levels. Pathological studies further confirmed the therapeutic effects of Mrl. Conclusion The results of this study demonstrate the promising therapeutic effects of Mrl against inhaled PQ in rats.